2017
DOI: 10.2147/idr.s147459
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence burden, and clinical impact of healthcare-associated infections and antimicrobial resistance: a national prevalent cohort study in acute care hospitals in Greece

Abstract: BackgroundAssessing the overall burden of healthcare-associated infections (HAIs) is challenging, but imperative in evaluating the cost-effectiveness of infection control programs. This study aimed to estimate the point prevalence and annual incidence of HAIs in Greece and assess the excess length of stay (LOS) and mortality attributable to HAIs, overall and for main infection sites and tracer antimicrobial resistance (AMR) phenotypes and pathogens.Patients and methodsThis prevalent cohort study used a nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 28 publications
(61 reference statements)
6
65
3
3
Order By: Relevance
“…The frequent types of HCAIs were lower respiratory tract infections (LRTIs), bloodstream infections, UTIs, SSIs, and systemic infections. 38 One systematic review and meta-analysis regarding HCAIs in Southeast Asian countries (Brunei, Myanmar, Cambodia, East Timor, Indonesia, Laos, Malaysia, the Philippines, Singapore, Thailand, and Vietnam) found an overall prevalence rate of 9.1% with the most common microorganisms being P. aeruginosa, the Klebsiella species, and Acinetobacter baumannii. 39 A study conducted in eight university hospitals of Iran (ranging from 60 to 700 beds) reported an overall HCAI frequency of 9.4%, the most common HCAIs were bloodstream infections, SSIs, UTIs, and pneumonia.…”
Section: Prevalence and Brief Outline Of Hcaismentioning
confidence: 99%
“…The frequent types of HCAIs were lower respiratory tract infections (LRTIs), bloodstream infections, UTIs, SSIs, and systemic infections. 38 One systematic review and meta-analysis regarding HCAIs in Southeast Asian countries (Brunei, Myanmar, Cambodia, East Timor, Indonesia, Laos, Malaysia, the Philippines, Singapore, Thailand, and Vietnam) found an overall prevalence rate of 9.1% with the most common microorganisms being P. aeruginosa, the Klebsiella species, and Acinetobacter baumannii. 39 A study conducted in eight university hospitals of Iran (ranging from 60 to 700 beds) reported an overall HCAI frequency of 9.4%, the most common HCAIs were bloodstream infections, SSIs, UTIs, and pneumonia.…”
Section: Prevalence and Brief Outline Of Hcaismentioning
confidence: 99%
“…More recently, the effort of the scientific community in developing NMs-based antimicrobial agents has been stimulated by the emergence of multi-drug-resistant pathogens, posing a world-wide challenge with a large socio-economic impact [28,29]. In particular, a major issue is due to microbe spreading by (1) cross-contamination through infected surfaces in nosocomial environments [30,31] (2) biofilm formation on the surfaces of medical implants, such as dental or bone repair devices [32][33][34][35][36]. Infectious diseases caused by fungi, viruses, bacteria, and particularly by multidrug resistant bacteria has an estimated annual cost (direct and indirect) ranging from 6 to 60 billion US$ [37] in the US only.…”
Section: Introductionmentioning
confidence: 99%
“…These infections occur during healthcare delivery for other diseases and even after discharge. HAIs are associated with prolonged hospital stay, poor prognosis, and increased mortality and economic burden [2][3][4]. A systematic review and meta-analysis reported that the major risk factors independently associated with HAIs were diabetes mellitus, immunosuppression, body temperature, surgery time in minutes, reoperation, cephalosporin exposure, days of exposure to central venous catheter, intensive care unit (ICU) admission, ICU stay in days, and mechanical ventilation [5].…”
Section: Introductionmentioning
confidence: 99%